Jackfruit (Artocarpus heterophyllus Lam.) seed flour as an alternative to cocoa powder in the production of chocolate cookies. - Eclarino, Hervie M.
This study utilized jackfruit seed flour as an alternative to cocoa powder in the production of chocolate cookies. Three formulations namely, F1 (40%), F2 (50%), and F3 (60%) were subjected to rank test for preference and F3 was determined as the most preferred formulation. The MPF was subjected to physico-chemical analyses, proximate analyses, and sensory evaluation. Physico-chemical analyses showed that the water activity and pH of the chocolate cookies were 0.43 and 6.91, respectively. The chocolate cookies produced from jackfruit seed flour had 1.76% moisture content, 1.11% ash content, 0.44% crude protein, 22.13% crude fat, 3.275% crude fiber, and 71.41% carbohydrate content. The chocolate cookies produced from jackfruit seed flour were perceived to be chocolate in color and had a very perceptible chocolate taste and aroma. Forty-two percent of the hundred (100) respondents rated the product as like extremely. This showed that the product had a promising marketability.